Kemampuan Siswa SMP dalam Menulis Bukti Ditinjau Berdasarkan Tingkat Kemampuan Matematika - Robbi Nur Mulyo; Mega Teguh Budiarto; Ismail; Rini Setianingsih (Pi: Mathematics Education Journal, 2023)
The ability to write proof means writing down an idea to prove a mathematical problem. It consists of a combination of the ability to read, write and prove. This study aims to describe the ability of junior high school students to write evidence based on mathematical ability. However, only students with high mathematical abilities are the subject of the research. This research is a descriptive study using a qualitative approach. Tests and interviews were conducted to collect the data. There were three steps for collecting data in this study: administering a mathematical ability test; administering a proof writing test with congruence questions to students with high mathematical abilities; and interviewing three students with high mathematical abilities of Grade IXA of SMP Negeri 1 Siliragung, Banyuwangi Regency. Data analysis includes data reduction, data presentation, and drawing conclusions. The results showed that students with high mathematical abilities had good reading, writing, and proving abilities. Based on the results of this study, the researchers suggest that teachers train students more often in reading, writing, and proving mathematical problems and accustom students to writing proofs systematically.